The Mediating Role of Interpersonal Relationship in the Effect of Emotional Competence on Prosocial Behaviour among Adolescents in Malaysia - Pung, Pit-Wan; Koh, Doh Hian; Tan, Soon Aun; Yap, Ming Hui (Makara Human Behavior Studies in Asia, 2021)
Prosocial behaviour has been regarded as a necessity for a society to function well. The present study aimed to examine the relationship between emotional competence, interpersonal relationship and prosocial behaviour among 496 school-going adolescents in Malaysia. The subjects were selected using Multistage Cluster Sampling method. Profile of Emotional Competence (PEC), Inventory of Parent and Peer Attachment Scale (IPPA) and Strength and Difficulties Questionnaires (SDQ) were used to measure emotional competence, interpersonal relationship with peers and adolescents’ prosocial behaviour respectively. The results showed that there were significant positive relationships among emotional competence, interpersonal relationship with peers and prosocial behaviour. Further analysis revealed that adolescents who reported having higher emotional competence tend to have a better interpersonal relationship with peers which in turn led to higher involvement in prosocial behaviour. Emotional competence and interpersonal relationship with peers are thus established as two important factors to promote prosocial behaviour among adolescents.